1997
DOI: 10.1088/0953-8984/9/7/020
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and electrical properties of the compounds

Abstract: The magnetization, a.c. susceptibility, resistivity and magnetoresistance have been measured for the invariable-unit-cell-parameter compounds. The Si substitution for Co in yields a dramatic initial increase of , whereas the 3d magnetic moment is reduced. These findings may be attributed to the strong involvement of Si p states in the hierarchy of exchange interactions. The magnetic phase transition at is of first order for the compounds with x < 0.075. For these compounds, the coexistence of metamagnetism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
(35 reference statements)
2
9
0
1
Order By: Relevance
“…They correspond to the fine amount of Ho-Co phases different from HoCo 2 formed during the diffusion annealing. The double peak in the ac susceptibility is in an agreement with similar measurements reported in [7] and it is ascribed to the first order transition in HoCo 2 at T C . The Mössbauer spectra taken at 293 K and 22 K are drawn in Fig.…”
Section: Resultssupporting
confidence: 91%
“…They correspond to the fine amount of Ho-Co phases different from HoCo 2 formed during the diffusion annealing. The double peak in the ac susceptibility is in an agreement with similar measurements reported in [7] and it is ascribed to the first order transition in HoCo 2 at T C . The Mössbauer spectra taken at 293 K and 22 K are drawn in Fig.…”
Section: Resultssupporting
confidence: 91%
“…Therefore, it is clear that there is no IEM in these Si-substituted compounds. It has been reported that in ErðCo 12x Si x Þ 2 [8] and HoðCo 12x Si x Þ 2 [11] the transition is FOT for x # 0:075 and it changes to SOT for x . 0:075: A similar variation has been observed in Alsubstituted RCo 2 compounds [9,12,13] as well.…”
Section: Resultsmentioning
confidence: 99%
“…26 and 27͒ alloys, where lattice parameter varies considerably. Similarly, in Ho͑Co 1−x Si x ͒ 2 diluted alloys 23 with invariable lattice parameter and in Ho͑Co 1−x Al x ͒ 2 alloys T C increases with x at the same rate, see Fig. 4͑b͒.…”
Section: A Variation Of the 3d-dos Upon Substitution Of Cobalt By Nomentioning
confidence: 61%
“…5. We should note that such behavior is common for many RCo 2 -based alloys, 23,26,[31][32][33][34][35] which include both,…”
Section: B Electrical Resistivitymentioning
confidence: 92%